Deconstruction of Legal Liability for Road Users in Whoosh Feeder Train Accidents at Unguarded Level Crossings - Hastiwi, Irine Sofa Nugri; Salsabila, Balqis; Izzati, Yayang; Margaretha, Zefanya (SIGn Jurnal Hukum, 2025)
The operation of the Whoosh Feeder Train at unguarded level crossings has triggered a series of fatal accidents that place road users as vulnerable accident victims. Ironically, victims face a protection disparity due to the limitations of state social insurance, which reduces recovery of property damage, as well as sectoral regulations that provide illusory protection for the operator. Therefore, this research aims to establish the legal standing of accident victims, deconstruct the assumption of human error into corporate systemic negligence, and formulate a civil liability scheme based on joint and several liability. This research is normative legal research using the statute and conceptual approaches, qualitatively and deductively analyzing various railway, traffic, and civil law regulatory instruments. The research results indicate that the absence of material damage recovery constitutes a denial of the utility and legal certainty principles. The schedule pressure of time integration (bundling) is proven to fail to fulfil the Railway Safety Management System, thereby shifting liability to PT Kereta Api Indonesia (Persero) under the vicarious liability doctrine. Furthermore, the absence of boom gates on the road constitutes a form of infrastructure omission (onrechtmatige overheidsdaad) by the Local Government, in violation of roadworthiness standards. This research concludes that state and corporate administrative negligence fully satisfies the elements of an unlawful act. As a recommendation, the judicial power must apply material damage lawsuits under joint and several liability through the instruments of Article 1365 juncto Article 1366 of the Civil Code, accompanied by comprehensive legislative revisions to restore justice (gerechtigkeit) for civil society.